ANALISIS PELAFALAN KARAKTER “DE” DALAM LAGU MANDARIN YANG DINYANYIKAN OLEH TERESA TENG - Yuk Ting (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2016)
From the previous research entitled “Analisis Pelafalan Karakter ? dalam Kumpulan Lagu Terbaik yang Dinyanyikan oleh Andy Lau”, it was found that the pronunciation of the characters ? changes variously into [t?] and [ti], which is caused by two factors, namely the position of the tongue (the rise and fall of the tongue), and factors of high and low tones. This study is a qualitative one aiming at describing the pronunciation of the character ?“DE” in the Chinese songs sung by Teresa Teng. In this study, the author took data from the songs sung by Teresa Teng, one of the legendary singers from Taiwan. In the songs, there is a phenomenon that is similar to what happened in the songs sung by Andy Lau, namely a change in the pronunciation of the characters ? was pronounced into [ti]. A professional singer certainly would apply the technique of good improvisation, to create harmonization between the tone and the lyrics of the song. This study used grammatical and phonological review to assess what kind of character ? pronunciation in the songs sung by Teresa Teng, then examined the factors that affect the pronunciation of the characters ?. The result showed that out of 22 samples taken from 10 songs sung by Teresa Teng, there is only one case that the character ?“DE” was pronounced into [t?], while the other 21 sampes were pronounced into [ti]. Compared to the previous research, it can be said that the position of the tongue and high and low tones don’t give the significant effect to the pronounciation of the character ?.